The Impact of the COVID-19 Pandemic on Breast Reconstruction: A Canadian Perspective. Issue 4 (November 2021) - Illmann, Caroline F.; Doherty, Christopher; Wheelock, Margaret; Vorstenbosch, Joshua; Lipa, Joan E.; Zhong, Toni; Isaac, Kathryn V.
Background: The COVID-19 pandemic has led to unprecedented challenges and restrictions in surgical access across Canada, including for breast reconstructive services which are an integral component of comprehensive breast cancer care. We sought to determine how breast reconstructive services are being restricted, and what strategies may be employed to optimize the provision of breast reconstruction through a pan-Canadian evaluation from the providers' perspective. Methods: This was a cross-sectional survey of Canadian plastic and reconstructive surgeons who perform breast reconstruction. The 33-item web-based questionnaire was developed by a pan-Canadian working group of breast reconstruction experts and disseminated via email to members of the Canadian Society of Plastic Surgery. The questionnaire queried respondents on the impact of the COVID-19 pandemic and associated restrictions on surgeons' breast reconstruction practice patterns and opinions on strategies for resource utilization. Results: Responses were received from 49 surgeons, who reported practicing in 8 of 10 Canadian provinces. Restrictions on the provision of breast reconstructive procedures were most limited during the First Wave of the COVID-19 pandemic, where all respondents reported at least some reduction in capacity and more than a quarter reporting complete cessation. Average reported reduction in capacity ranged from 31% to 78% across all 3 waves. Autologous, delayed, and prophylactic reconstructions were most commonly restricted. Conclusion: This study provides a pan-Canadian impact assessment on breast reconstructive services during the COVID-19 pandemic from the providers' perspective. To uphold the standards of patient-centred care, a unified approach to strategically reorganize health care delivery now and in the future is needed.